Structure–activity relationships of voltaglue organic blends - Tan, Nigel Chew Shun (2020)
Voltage‐activated, one‐pot adhesives are an emerging platform with many potential advantages, but require multicomponent grafting of electrochemical donors and acceptors for operation in organic environments. This formulation strategy reduces throughput efficiency, organic solubility, and requires additional purification of the grafted dendrimers. A more advanced strategy is proposed for setting up the donor–acceptor conductive network by exploiting a flexible blending design, providing faster throughput of structure–activity analyses with less synthetic investment. The blend method investigates the ampere‐dependent storage modulus and gelation time as a function of both donor and acceptor concentration. This blend strategy allows a rapid evaluation of donor–acceptor parameters involved in voltage‐activated adhesive formulations.